Thruster Modelling for Underwater Vehicle Using System Identification Method. (21st May 2013) - Aras, Mohd Shahrieel Mohd; Abdullah, Shahrum Shah; Rahman, Azhan Ab.; Aziz, Muhammad Azhar Abd
Abstract This paper describes a study of thruster modelling for a remotely operated underwater vehicle (ROV) by system identification using Microbox 2000/2000C. Microbox 2000/2000C is an XPC target machine device to interface between an ROV thruster with the MATLAB 2009 software. In this project, a model of the thruster will be developed first so that the system identification toolbox in MATLAB can be used. This project also presents a comparison of mathematical and empirical modelling. The experiments were carried out by using a mini compressor as a dummy depth pressure applied to a pressure sensor. The thruster model will thrust and submerge until it reaches a set point and maintain the set point depth. The depth was based on pressure sensor measurement. A conventional proportional controller was used in this project and the results gathered justified its selection.